THE REALITY OF PRESERVING AND PROMOTING THE GENTLE, ELEGANT, AND HOSPITABLE STYLE OF DALAT PEOPLE - Võ Thuấn; Trần Thị Minh Phương (Tạp chí Khoa học Đại học Đà Lạt)
In the process of building and developing the city DaLat, its citizens have always been gentle, elegant, and hospitable. The purpose of this article is to analyze and systemize the advantages, achievements as well as drawbacks and limitations in preserving and promoting the gentle, elegant, and hospitable style of living of DaLat people, using secondary documents, qualitative, and quantitative data through surveys. Besides the detailed description of these characteristics, an analysis of factors that positively and negatively affect the preservation and promotion of DaLat people's style is also emphasized. At the same time, the paper shows how the subjects have fulfilled their responsibilities to preserve and promote the style of DaLat people in the process of integration and development.